اتفاق الشراكة بين الجزائر والاتحاد الأوروبي - واقع وآفاق - إبراهيم, مناني; عمارة, عبيدي (University of eloued جامعة الوادي, 2021)
"في بداية التسعينات سعى الاتحاد الأوروبي إلى طرح مشروع الشراكة من خلال مؤتمر برشلونة الذي يوضح فيه السياسة الجديدة للاتحاد مع دول جنوب المتوسط ، ولقد نتج عن هذا العمل تطور في إبرام عدة اتفاقيات ثنائية مع دول الضفة الجنوبية للمتوسط ، فهذه الاتفاقيات تهدف إلى إقامة فضاء أورو متوسطي من خلال منطقة التبادل الحر بين الضفتين للمتوسط متماشيا مع مبادئ المعاملة بالمثل الناجم عن أسس المنظمة العالمية للتجارة. والجزائر كغيرها من البلدان المتوسطية قامت بإمضاء عقد الشراكة مع الاتحاد الأوروبي كحلقة للاندماج في سيرورة الاقتصاد العالمي، بهدف تحقيق أهداف تنموية على المدى الطويل بالرغم من التكاليف الانتقالية المحتملة والإفرازات السلبية. وانطلاقا لما ورد نحاول من خلال هذه الدراسة تحليل واقع الاقتصاد الجزائري ومدى قدرته على الانسجام مع متطلبات الشراكة من خلال وضعية التجارة الخارجية باعتبارها العامل المهم في الاتفاقية، ووضعية رؤوس الأموال الأجنبية التي تعتبر محرك التنمية الاقتصادية والاجتماعية.""In the early nineties, the European Union sought to put forward a partnership project through the Barcelona Conference, in which it clarifies the new policy of the union with the countries of the southern Mediterranean. This work resulted in a development in the conclusion of several bilateral agreements with the countries of the southern bank of the Mediterranean. These agreements aim to establish a Euro-Mediterranean space through the free trade area between the two shores of the Mediterranean in line with the principles of reciprocity resulting from the foundations of the World Trade Organization. Algeria, like other Mediterranean countries, has signed a partnership contract with the European Union as a link for integration into the global economic process with the aim of achieving long-term development goals, despite the potential transitional costs and negative outcomes. Based on what was mentioned, we try, through this study, to analyze the reality of the Algerian economy and its ability to be in harmony with the requirements of partnership through the status of foreign trade as the important factor in the agreement, and the status of foreign capital, which is the engine of economic and social development."
مذكرة ماستر تجارة دولية
Keywords: اتفاق الشراكة، منطقة التبادل الحر، التجارة الخارجية، الاستثمار الأجنبي; Partnership Agreement, Free Trade Area, Foreign Trade, Foreign Investment